An exploratory analysis of Early Adopters in education innovations - Lindsey Devers Basileo; Merewyn Elizabeth Lyons (Quality Education for All)
Purpose – The purpose of this study is to gain a better understanding of the conditions and motivations that influence teachers to adopt innovations. Design/methodology/approach – Using Diffusion of Innovation theory (Rogers, 2003) and Self-Determination theory (Ryan and Deci, 2017), data from two surveys (n = 568; n = 108) and qualitative follow-up interviews of Early Adopter teachers (n = 16) were triangulated to discern relationships among their identification as Early Adopters, satisfaction of their basic psychological needs (BPN) and their implementation of an educational innovation. Findings – Early Adopters had a positive and statistically significant relationship with the implementation of the innovation. Satisfaction of teachers’ BPN had the largest impact on innovation. Research limitations/implications – The findings are preliminary and based on a small sample size of teachers. Reliability of the measure of BPN was not as high as the standard, but it did have the largest impact on implementation. Additional studies should explore the connections among Early Adopter teacher motivation, leadership and the satisfaction of their BPN. Practical implications – School leaders should leverage the influence of Early Adopters to support innovation, and they should provide additional time, training and resources to supports teachers’ BPN. Originality/value – This study examines how to identify and support Early Adopter teachers as enablers of change within schools. We know of no other studies that have used both Diffusion of Innovation theory and Self-Determination theory to understand the motivations of Early Adopter teachers.